2006
DOI: 10.1016/j.ijsolstr.2005.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of localized failure in low-basis-weight paper

Abstract: Continuum damage mechanics (CDM) is used to describe the post-elastic behavior of low-basis-weight paper. The relevance of undertaking studies of the mechanical behavior of low-basis-weight paper is that it enables characterization, optimization and quality control. In accordance with a CDM theory, an internal variable is introduced that represent the degree to which the material has degraded in a continuum sense and details inherent in a damage evolution law contain information about the rupture mechanism. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
5
20
0
Order By: Relevance
“…Fundamental works and review articles have described key aspects (Linhart et al 1987;Deng and Dodson 1994;Niskanen and Leskela 1997;Niskanen and Kärenlampi 1998). Also, progress has been achieved in terms of mathematical models to bridge the gap between paper structure and the damage leading to breakage that occurs on a local level within the structure (Korteoja et al 1997;Niskanen and Leskela 1997;Kotik et al 2005;Hagglund and Isaksson 2006). Certain studies that set out to demonstrate benefits of dry-strength additives have shown, probably to the surprise of the researchers, that some effects of the additives could be accounted for based on changes in the uniformity of the resulting paper (Roberts et al 1986;Kim and Hubbe 2010).…”
Section: Formation Uniformitymentioning
confidence: 99%
“…Fundamental works and review articles have described key aspects (Linhart et al 1987;Deng and Dodson 1994;Niskanen and Leskela 1997;Niskanen and Kärenlampi 1998). Also, progress has been achieved in terms of mathematical models to bridge the gap between paper structure and the damage leading to breakage that occurs on a local level within the structure (Korteoja et al 1997;Niskanen and Leskela 1997;Kotik et al 2005;Hagglund and Isaksson 2006). Certain studies that set out to demonstrate benefits of dry-strength additives have shown, probably to the surprise of the researchers, that some effects of the additives could be accounted for based on changes in the uniformity of the resulting paper (Roberts et al 1986;Kim and Hubbe 2010).…”
Section: Formation Uniformitymentioning
confidence: 99%
“…The initial studies of the structural performance of nonwoven fabrics were focused on paper (Bronkhorst, 2003;Hägglund and Isaksson, 2006;Isaksson et al, 2006Isaksson et al, , 2004 but more recent analyses have dealt with glass (Ridruejo et al, 2010), polyamide (Silberstein et al, 2012), polypropylene (Farukh et al, 2013;Jubera et al, 2014;Ridruejo et al, 2011Ridruejo et al, , 2015 and polyethylene (Martínez-Hergueta et al, 2015;Raina and Linder, 2014;Raval et al, 2013) nonwoven fabrics. These investigations found that the micromechanisms of deformation and fracture depend on the interaction of a number of factors including fiber uncurling, bond failure and fiber reorientation as well as fiber sliding and fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Hägglund and Isaksson 2006;Isaksson and Hägglund 2007a), it is reported that classical continuum mechanical descriptions of paper materials cannot fully describe deformations near macroscopic cracks. This is due to microstructural effects altering the strain field in the body if it is inhomogeneous; the fibers introduce long-ranging actions that limit the size of gradients in strain.…”
Section: A Nonlocal Continuum Field Theory: the Implicit Gradient Appmentioning
confidence: 99%
“…Heyden and Gustafsson 1998; Ritala and Huiku 1989;Åström and Niskanen 1993;Fig. 1 Fracture testing of tissue paper for two pre-fabricated slit lengths, 5 mm (a) and 70 mm (b) for a specimen size of 230 × 150 mm Hägglund and Isaksson 2007). It is observed in experiments on paper that for networks having anopen (sparse) structure, a relatively large macroscopic crack is required to localize macroscopic failure (Hägglund and Isaksson 2006). Figure 1 illustrates the difference in behavior between an initial crack length of 5 mm and 70 mm for a tissue paper material.…”
Section: Introductionmentioning
confidence: 99%